2015
DOI: 10.5455/aim.2015.23.268-272
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Sonographically Demonstrated Ureteral Dilatation in Evaluation of Vesicoureteral Reflux Verified with Voiding Urosonography in Children with Urinary Tract Infection

Abstract: Objectives:The aim of this study was to determine sensitivity, specificity, and predictive values of sonographically demonstrated ureteral dilatation in detecting vesicoureteral reflux (VUR).Methods:Ethical approval from the Ethical Committee of Clinical Center University of Sarajevo and parental consent were obtained for this prospective study involving 120 children with history of urinary tract infections (UTIs). Ultrasound examination included the evaluation of the urinary tract, with a special emphasis on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In the present study, children who were demonstrated to be negative for VUR by CeVUS examination were also negative for VUR in the VCUG examination, while 2 children who were determined to be negative for VUR by VCUG were later diagnosed with unilateral Grade III VUR using CeVUS scanning. These results are consistent with a previous study ( 23 ) and suggest that VCUG is not sensitive enough to diagnose Grade III VUR due to its intermittent scanning ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, children who were demonstrated to be negative for VUR by CeVUS examination were also negative for VUR in the VCUG examination, while 2 children who were determined to be negative for VUR by VCUG were later diagnosed with unilateral Grade III VUR using CeVUS scanning. These results are consistent with a previous study ( 23 ) and suggest that VCUG is not sensitive enough to diagnose Grade III VUR due to its intermittent scanning ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…But others believe that VCUG must be done as soon as possible. After VUS is introduced, the number of VCUG investigations were reduced by over half and, consequently, a significant reduction of radiation exposure in children can be achieved [22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…At Baruch-Padeh Poria Medical Center, we are performing all these imaging tests as following: In children with age less than half year, renal US is recommended during admission or nearby. If the ultrasound is abnormal and if there is no response to treatment with antibiotics during 48 hrs, VCUG must be performed during the coming two weeks [24][25][26][27], and renal scan 3 to 5 months after the UTI [28]. Children with age above half year, ultrasound will be performed first, and renal DMSA scan few months later [26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation